Generating Irregular Models for 3D Spherical-Particle-Based Numerical Methods - Gang-Hai Huang; Yu-Yong Jiao; Xiu-Li Zhang; Amoussou-Coffi Adoko; Shu-Cai Li (Journal of Applied Mathematics)
The realistic representation of an irregular geological body is essential to the construction of a particle simulation model. A three-dimensional (3D) sphere generator for an irregular model (SGIM), which is based on the platform of Microsoft Foundation Classes (MFC) in VC++, is developed to accurately simulate the inherent discontinuities in geological bodies. OpenGL is employed to visualize the modeling in the SGIM. Three key functions, namely, the basic-model-setup function, the excavating function, and the cutting function, are implemented. An open-pit slope is simulated using the proposed model. The results demonstrate that an extremely irregular 3D model of a geological body can be generated using the SGIM and that various types of discontinuities can be inserted to cut the model. The data structure of the model that is generated by the SGIM is versatile and can be easily modified to match various numerical calculation tools. This can be helpful in the application of particle simulation methods to large-scale geoengineering projects.